REVIEW OF RUSSIAN ARCHIVES ON SOVIET-CZECH RELATIONS - A. N. Artizov (Vestnik MGIMO-Universiteta)
The author addresses the problem of the role and place of archives in the process of political identity formation, including in the field of “politics of memory.” The article draws attention to the fact that the prevailing notions about archives imply a static understanding of the role and functioning of archives. Instead, the author challenges those assumptions and suggests examining the archives as part of a wide network of institutions of public diplomacy, which forge and nurture mutual understanding and cooperation in the humanitarian sphere. To confirm the stated thesis, the article refers to the joint activities and activities of Russian archives in the framework of Russian-Czech relations, examines in detail the questions of historical memory and complex historical issues in the history of Russian-Czech relations. The article analyzes the current state of the archives on Soviet-Czech relations, the trends in the declassification of archival materials. Particular attention is given to the reflection of bilateral relations in archival documents in 1918, 1938 and 1968. The author concludes that the declassification of documents on problematic issues of bilateral relations does not lead to an automatic improvement of mutual understanding, since the parties may have conflicting interpretations of the same documents.